Eosinophils: The unsung heroes in cancer?. (1st February 2018) - Varricchi, Gilda; Galdiero, Maria Rosaria; Loffredo, Stefania; Lucarini, Valeria; Marone, Giancarlo; Mattei, Fabrizio; Marone, Gianni; Schiavoni, Giovanna
ABSTRACT: Prolonged low-grade inflammation or smoldering inflammation is a hallmark of a cancer. Eosinophils are components of the immune microenvironment that modulates tumor initiation and progression. Although canonically associated with a detrimental role in allergic disorders, these cells can induce a protective immune response against helminthes, viral and bacterial pathogens. Eosinophils are a source of anti-tumorigenic (e.g., TNF-α, granzyme, cationic proteins, and IL-18) and protumorigenic molecules (e.g., pro-angiogenic factors) depending on the milieu. In several neoplasias (e.g., melanoma, gastric, colorectal, oral and prostate cancer) eosinophils play an anti-tumorigenic role, in others (e.g., Hodgkin's lymphoma, cervical carcinoma) have been linked to poor prognosis, whereas in yet others they are apparently innocent bystanders. These seemingly conflicting results suggest that the role of eosinophils and their mediators could be cancer-dependent. The microlocalization (e.g., peritumoral vs intratumoral) of eosinophils could be another important aspect in the initiation/progression of solid and hematological tumors. Increasing evidence in experimental models indicates that activation/recruitment of eosinophils could represent a new therapeutic strategy for certain tumors (e.g., melanoma). Many unanswered questions should be addressed before we understand whether eosinophils are an ally, adversary or neutral bystanders in different types of human cancers.